The genera Melyvonnea gen. nov. and Mesophyllum s.s. (Melobesioideae, Corallinales, Rhodophyta) particularly from the central Atlantic Ocean. (22nd May 2014) - Athanasiadis, Athanasios; Ballantine, David L.
<x xml:space="preserve">Abstract</x> We propose the new genus Melyvonnea to accommodate species previously included in Mesophyllum having: a) perithallial protuberances that may branch and dominate over the encrusting base, b) monoecious gametophytes with gametangial conceptacles occasionally developed in superimposition, c) spheroid carposporangial chambers (lacking a central pedestal), and d) filaments lining canals of multiporate roofs composed of 3 to 5 cells with distinctively elongate basal cells. The new genus shares with Mesophyllum the development of a predominantly coaxial hypothallium. Melyvonnea presently accommodates three species in the Central Atlantic, viz. the generitype Melyvonnea canariensis (Foslie) comb. nov. from the Canary Islands, Melyvonnea erubescens (Foslie) comb. nov. ( = Mesophyllum incertum; type locality: Bermuda) from the western Atlantic, Melyvonnea aemulans (Foslie & Howe) comb. nov. from Puerto Rico, and one Indo‐Pacific species, Melyvonnea madagascariensis (Foslie) comb. nov. We also emend Mesophyllum Lemoine to encompass Northern Hemisphere species that lack the above apomorphies of Melyvonnea and in addition develop a central pedestal in carposporangial conceptacles (via dissolution of the surrounding cells) with gonimoblasts bending down to fill the empty space. Mesophyllum sensu stricto currently includes six species in the northeast Pacific (M. aleuticum, M. conchatum, M. crassiusculum, M. lamellatum, M. megagastri, M. vancouveriense), two species in the western Atlantic (M. mesomorphum and M. syntrophicum), and three species in the northeast Atlantic and the Mediterranean Sea (M. expansum, M. lichenoides, M. philippii). Gametophytic species of each genus show a mainly disjunct distribution being restricted to the tropics–subtropics (Melyvonnea) and the temperate waters of the Northern Hemisphere (Mesophyllum s.s.). This classification is supported by a consensus of studies of all well‐known species of Mesophyllum sensu Adey (1970), and is based on a phylogenetic analysis of morphological and anatomical characters in addition to molecular evidence.